Participatory Planning in the Special Allocation Fund Preparation Process in Sleman Regency, Special Region of Yogyakarta - Wicaksono, Ragil; Sabihaini, Sabihaini; Kristanto HC, R Heru (Technium Social Sciences Journal, 2024)
The theory and practice of urban planning have both shown a significant amount of attention in regards to community participation. Numerous studies have added to the growing body of literature highlighting the benefits of community participation in city planning and management. On the other hand, the literature on participation contains just a handful of theory-based empirical studies that investigate the role of community participation in the planning process of special fund programs in the Special Region of Yogyakarta. This research method uses quantitative analysis involving data collection using probability sampling techniques to collect data from 64 respondents. After that, a survey was conducted with the help of a questionnaire that was given out to respondents in order to obtain sample data. After that, the data that was gathered were examined by means of multiple regression analysis, which was carried out with the assistance of the SPSS Statistics 25 program. The results of this study indicate that knowledge, awareness, social media, political culture, and education have a positive and significant effect on community participation. This shows that active community participation in the special fund preparation program in the Special Region of Yogyakarta can be more targeted according to community needs.